The Great population hoax (s.n., 1980)
An evaluation of the population problem which includes birth control, economics, food production and attitudes of third world countries. Part 1 explains the cause and effect of population growth. Part 2 shows the network of organizations involved in planned parenthood and the critics of population control programs in developing countries and among women's organization.